Stroke and physiological relationships during the incremental front crawl test: outcomes for planning and pacing aerobic training - Almeida, T. A.; Espada, M. C.; Massini, D. A.; Macedo, A. G.; Castro, E. A.; Ferreira, C. C.; Reis, J. F.; Pessôa Filho, D. M. (Frontiers in Physiology, 2023)
Purpose: This study aimed to evaluate the physiological responses associated with the stroke length (SL) and stroke rate (SR) changes as swimming velocity increases during an incremental step-test. Moreover, this study also aimed to verify if SL and SR relationships toward maximal oxygen uptake (VO2max), gas respiratory compensation point (RCP), exchange threshold (GET), and swimming cost can be applied to the management of endurance training and control aerobic pace.